Putting Names on People and Using Shame as a Form of Punishment and Fun - Laiba Habib (Research Journal of Psychology, 2024)
As a tool for administering criminal justice, shame has a checkered past since it has been used by various branches of government in a variety of different contexts and configurations over the course of history. Despite this, the act of humiliation has been given a greater platform in the later half of the twentieth century by the mass media, ostensibly for the purpose of providing pleasure and reducing the incidence of criminal behavior. This essay provides a context for the phenomenon of mass-mediated humiliation by situating it within the greater framework of popular culture and the legal system. The use of popular culture as a way to humiliate is a crucial technique that serves as a means of reinforcing prevalent societal notions about crime and criminal behavior. However, it also possesses a subversive power that presents a challenge to regimes that want to use shame as a tool for social manipulation or economic profit. This capacity is a result of the fact that shame is a universal human experience. Dateline NBC: To Catch a Predator, an American tabloid news platform that is internationally recognized, serves as an informative case study to highlight the complicated cultural context around the concept of shame. Keywords: intimidation, public scrutiny, virtual anonymity, predators, and vigilantism